Proceedings of the 43rd Annual Symposium on Frequency Control
DOI: 10.1109/freq.1989.68889
|View full text |Cite
|
Sign up to set email alerts
|

Residual phase noise measurements of VHF, UHF, and microwave components

Abstract: The results of residual phase noise measurements on a number of VHF, UHF, and microwave amplifiers, both silicon bipolar junction transistor (BJT) and GaAs field effect transistor (FET) based, electronic phase shifters, frequency dividers and multipliers, etc., which are commonly used in a wide variety of frequency source and synthesizer applications are presented. The measurement technique has also been used to evaluate feedback oscillator components, such as the loop and buffer amplifiers, which can play i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The residual phase noise measurement techniques [7] are employed to evaluate the components of loop amplifier, STW resonator and electronic phase shifter. The noise floor of the measurement system is about -170dBc/Hz with 1/f flicker noise corner at 17kHz offset.…”
Section: Oscillator Designmentioning
confidence: 99%
“…The residual phase noise measurement techniques [7] are employed to evaluate the components of loop amplifier, STW resonator and electronic phase shifter. The noise floor of the measurement system is about -170dBc/Hz with 1/f flicker noise corner at 17kHz offset.…”
Section: Oscillator Designmentioning
confidence: 99%
“…The baseband shaping of the low frequency noise may explain the anomalous "bumps" observed in [10]. It has been shown that, although the signal frequency may be relatively high, the appropriate circuit models must be used to predict baseband shaping accurately.…”
Section: B Low Offset Frequency Noise Shapingmentioning
confidence: 99%
“…As in the amplifier case, we find that there is often a l/f component of AM and PM noise of nearly equal amplitude. Close to the camer the l/f3 PM noise dominates as is generally accepted [2,4,8]. There has been speculation that PM to AM conversion with the oscillator would cause the AM noise close to the carrier to vary as l/f3.…”
Section: Introductionmentioning
confidence: 89%
“…Specific samples often deviate from the models, but they still give us a better insight into the total noise process within the device. The noise model for X-band double balanced mixers is similar to that of rf mixers [4,5]. The noise models for amplifiers are, to our knowledge, the first to show that the PM and AM noise added by an amplifier originates from two common sources.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation